Penguatan Identitas Nasional dan Cinta Tanah Air melalui Digital Legal Empowerment bagi Anak Pekerja Migran pada KKN Internasional Sanggar Belajar di Sungai Buloh Selanggor Malaysia - Bagas Dava Aji Ramadhan; Alfian Hidayat; Calvin Andika Putra; Aris Prio Agus Santoso (Jurnal Informasi Pengabdian Masyarakat, 2026)
The community service program through the International Community Service Program (KKN Internasional) at Sanggar Belajar Sungai Buloh Selanggor Malaysia was motivated by the low understanding of national identity, legal awareness, and digital literacy among children of Indonesian migrant workers in Malaysia. This condition is influenced by limited access to civic education and the diaspora environment, which exposes students more to foreign cultures than Indonesian national values. This program aimed to strengthen national identity and foster patriotism through a Digital Legal Empowerment approach based on digital literacy and basic legal education. The method used was Participatory Action Research (PAR) with differentiated learning and a Hybrid-Analog approach through interactive digital media, group discussions, simulations, and participatory mentoring. The results showed an increase in student participation in the learning process, understanding of national symbols, citizens’ rights and obligations, and the use of digital media for educational purposes. In addition, the program encouraged the emergence of local leaders within the learning community who assisted the learning process and promoted a collaborative learning culture. This community service program demonstrates that the integration of digital literacy and legal education can be an effective strategy to strengthen nationalism, improve legal awareness, and create social transformation among children of Indonesian migrant workers in Malaysia.